Pentagalloylglucose, isolated from the leaf extract of Anacardium occidentale L., could elicit rapid and selective cytotoxicity in cancer cells - Bamigboye J. Taiwo; Temidayo D. Popoola; Fanie R. van Heerden; Amos A. Fatokun (BMC, 2020)
ABSTRACT Background The leaf of Anacardium occidentale L. has been a component of many herbal recipes in South-Western Nigeria. The work reported herein, therefore, explored the phytochemical composition of this plant and the potential anti-cancer activity of an isolated chemical constituent. Methods Phytochemical methods (including chromatographic analysis) combined with spectroscopic and spectrometric analyses (IR, HRMS and NMR (1D and 2D)) were used to identify chemical constituents. Cytotoxic effects were determined using the MTT viability assay and bright-field imaging. Induction of oxidative stress was determined using the fluorescence-based 2',7'-dichlorofluorescein diacetate (DCFDA) assay. Results For the first time in the plant, Compound 1 was isolated from the leaf extract and identified as pentagalloylglucose. Compound 1 was significantly cytotoxic against the cancer cell lines HeLa (human cervical adenocarcinoma cell line) and MRC5-SV2 (human foetal lung cancer cell line), with IC50 of 71.45 and 52.24 μg/ml, respectively. The selectivity index (SI) for Compound 1 was 1.61 (IC50 against the normal human foetal lung fibroblast cell line MRC-5 was 84.33μg/ml), demonstrating better cancer cell-selectivity compared to doxorubicin with a SI of 1.28. The cytotoxic activity of Compound 1 in HeLa cells was also rapid, as shown by its concentration- and time-dependent 3 h and 6 h cytotoxicity profiles, an effect not observed with doxorubicin. Generation of reactive oxygen species at high concentrations of pentagalloylglucose to induce oxidative stress in cancer cells was identified as a mechanistic event that led to or resulted from its cytotoxicity. Conclusions We suggest that pentagalloylglucose is selectively cytotoxic to cancer cells, and at high concentrations could exhibit pro-oxidant effects in those cells, as opposed to its general anti-oxidant effects in cells. Also, the presence of Compound 1 (pentagalloylglucose) in the plant and its cancer cell-selective cytotoxicity provide some rationale for the ethno-medicinal use of the plant's leaf extract for treating diseases associated with excessive cell proliferation. Further studies are required to dissect the molecular mechanisms and players differentially regulating the biphasic anti-oxidant and pro-oxidant effects of pentagalloylglucose in normal and cancer cells.